2008
DOI: 10.1111/j.1365-2958.2008.06225.x
|View full text |Cite
|
Sign up to set email alerts
|

Fold and function of polypeptide transport‐associated domains responsible for delivering unfolded proteins to membranes

Abstract: SummaryMembranes of Gram-negative bacteria, mitochondria and chloroplasts receive and fold b-barrel transmembrane proteins through the action of polypeptide transport-associated (POTRA) domains. In Escherichia coli, folding substrates are inserted into the outer membrane by the essential protein YaeT, a prototypic Omp85 protein. Here, the articulation between tandem POTRA domains in solution is defined by nuclear magnetic resonance (NMR) spectroscopy, indicating an unprecedented juxtaposition. The novel soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
179
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(188 citation statements)
references
References 42 publications
9
179
0
Order By: Relevance
“…However, this conclusion does not imply that each of the >50 different OMPs present in the OM specifically requires BamD for its assembly (39). Other components of the Bam complex also interact with substrates (13,15,(19)(20)(21)(22)38) and may have functions that overlap with that of BamD such that certain OMPs can be assembled in its absence. Rather, we suggest that BamD's essentiality in substrate binding reflects a kinetic effect on In the in vitro experiments, full-length BamA substrates containing mutations in the β-signal sequence were denatured and then diluted into solutions containing 0.5% lauryldimethylamine-N-oxide (LDAO) or BamABCDE proteoliposomes to assess, respectively, the effects of the mutations on the stability of the folded β-barrel and on the folding mechanism carried out by the Bam complex.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, this conclusion does not imply that each of the >50 different OMPs present in the OM specifically requires BamD for its assembly (39). Other components of the Bam complex also interact with substrates (13,15,(19)(20)(21)(22)38) and may have functions that overlap with that of BamD such that certain OMPs can be assembled in its absence. Rather, we suggest that BamD's essentiality in substrate binding reflects a kinetic effect on In the in vitro experiments, full-length BamA substrates containing mutations in the β-signal sequence were denatured and then diluted into solutions containing 0.5% lauryldimethylamine-N-oxide (LDAO) or BamABCDE proteoliposomes to assess, respectively, the effects of the mutations on the stability of the folded β-barrel and on the folding mechanism carried out by the Bam complex.…”
Section: Discussionmentioning
confidence: 94%
“…The POTRA domains bind the other four components of the assembly complex, BamB-E, which are lipoproteins. Structural and biochemical studies have suggested that the POTRA domains, BamB, and BamD may interact with substrate proteins during their assembly (13,15,(19)(20)(21)(22). However, more detailed information is required about the nature of those interactions and whether they are critical in the assembly process to develop an integrated mechanistic model.…”
mentioning
confidence: 99%
“…YaeT (also known as Omp85) is an essential OMP with a large periplasmic domain containing 5 polypeptide-transport-associated (POTRA) domains (32). Recent data suggest that these POTRA domains recognize unfolded OMPs and may serve to nucleate the formation of ␤-strands in OMPs before their membrane insertion (33)(34)(35). Importantly, there is no ATP in the periplasm that could be used to power the unfolding of proteins before their insertion in the membrane.…”
Section: Skp Prevents the Aggregation Of Ompa By Forming A Stable Commentioning
confidence: 99%
“…A conformational change similar to that in BamA x-ray structures was proposed for full-length FhaC by electron paramagnetic resonance (EPR) spectroscopy (32). Analysis of the orientation and conformational flexibility of the POTRA domains of BamA by solution and solid-state NMR, EPR, or small-angle x-ray scattering measurements revealed a rigid connection between ecP1 and ecP2 with a reorientation at timescales not detectable by these experimental methods, especially in lipid bilayers (13,31,33,34). Similarly, ecP4-ecP5 has a stable/rigid conformation in lipid bilayers as well as in detergent (31,35,36), which is similar to the x-ray structure of those domains.…”
Section: Introductionmentioning
confidence: 76%
“…In turn, the first, and thus most N-terminal, POTRA domain is an essential interaction partner of SurA, which has been proposed to deliver b-barrel proteins from the plasma membrane to the BAM complex (12). In line with this, NMR titration experiments revealed that ecP1 (for POTRA 1 of the E. coli protein BamA) and ecP2 interact with peptides comprising transmembrane b-strands of PhoE, which itself is a substrate of the BAM complex (13).…”
Section: Introductionmentioning
confidence: 82%